1993
DOI: 10.1152/ajpheart.1993.265.2.h666
|View full text |Cite
|
Sign up to set email alerts
|

Electrically stimulated contraction accelerates protein synthesis rates in adult feline cardiocytes

Abstract: Cardiocytes were induced to contract via electrical field stimulation with an 8 V/cm electrical square-wave pulse of 5 ms at 0.125-2.0 Hz for up to 6 h. Protein synthesis rates were measured as rate of incorporation of [3H]-phenylalanine into total cell protein. Rates of protein synthesis were accelerated 43 +/- 4%, P < 0.001, by 4 h. The acceleration of total protein synthesis showed a frequency dependence between 0.125 and 0.5 Hz. In addition to accelerating rates of total protein synthesis, electrical stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…In previous studies employing adult feline cardiocytes in primary culture, we demonstrated that electrically stimulated contraction resulted in an acute acceleration of both total protein synthesis and MHC synthesis rates (6). Two lines of evidence suggested that this acceleration occurred via a mechanism involving an increase in translational activity.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…In previous studies employing adult feline cardiocytes in primary culture, we demonstrated that electrically stimulated contraction resulted in an acute acceleration of both total protein synthesis and MHC synthesis rates (6). Two lines of evidence suggested that this acceleration occurred via a mechanism involving an increase in translational activity.…”
mentioning
confidence: 78%
“…Electrical Stimulation Model-Adult feline cardiocytes were obtained by collagenase digestion in combination with mechanical agitation as described previously (6,8,9). Following cell isolation, the Ca 2ϩ -tolerant cardiocytes were placed in Life Technologies, Inc. M199 serumfree medium with Earle's salts at a concentration of 50,000 rod-shaped cells/ml.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations